Ensaios sobre educação e mercado de trabalho do jovem - Ciriaco, Juliane da Silva (2022)
This Thesis is composed of three Essays that try to deepen and theoretically and empirically understand important aspects of youth dynamics in the world of work. Essay 1 seeks to investigate, in an innovative way, “how” and “to what extent” religious beliefs and practices can influence the values, opinions, perceptions and social attitudes of young people. In view of this, this research aims to understand the importance of the intensity of religious practice on the motivation of young Brazilians to search for work, using data from the 2013 National Health Survey (PNS). in the Extended Regression Model (ERM), more specifically the probit with ordinal endogenous treatment. Roughly speaking, estimates indicate that religion improves the incentive to come out of total inactivity and seek occupational engagement, especially among individuals with high religious attendance. In summary, the estimates of the average treatment effect model show evidence that religiosity has beneficial effects on the incentive to search for a job, that is, it is observed that participating in religion in a moderate way compared to no frequency increases the chance search for work by 28 percentage points (p.p.). For young people who participate with high intensity compared to no participation, it was observed that the search for a job rises, by approximately 53 p.p. The Essay 2, in turn, aims to empirically investigate the main determinants of leaving unemployment for an occupation or discouragement in Brazil in the periods before and after the first appearance of Covid-19. The econometric approach used consists of estimating, through the binary response model, the probability of a young person initially unemployed to move to the final position of occupied or discouraged in the last quarter of 2018, 2019 and 2020, using data from the National Continuous Household Sample Survey (PNADC), analyzed separately. In order to obtain a richer analysis of the economic scenario in Brazil, it is considered, in addition to the juvenile age group, the analysis of individuals in adulthood. Additionally, in order to verify the impact of the pandemic on the exit from unemployment for each of the statuses already mentioned here, the non-linear decomposition is performed, commonly used in order to observe the factors responsible for the differences in probabilities at the moment. before and after the first appearance of the SARS-CoV-2 virus. The results of the first part of the research show that, for both stages of life, being male and being employed at home increases the probability of leaving unemployment and finding a job. Furthermore, it was observed that the longer the period of unemployment, the greater the difficulty in finding an economic activity. In the second model that investigates the transition to despondency, it was observed that residing in urban areas, regardless of age group, reduces the probability of transitioning to despondency, before and after the pandemic outbreak. Regarding the sex of the individual, it can be seen in the year 2020 that the probability of entering into inactivity is reduced among men in adulthood. It should also be noted that, in the current pandemic moment, schooling has become essential for young people to leave unemployment and enter an occupation. In turn, for adults, educational qualification was of paramount importance only to reduce the chances of discouragement, representing a reduction of approximately 4 p.p. at the time of the pandemic. Finally, the differences in probability between the years 2019 and 2020 show a drop of 16 p.p. in the transition to an occupation for young people and 18 p.p. for adults. Regarding the transition to despondency, findings showed a drop in transition for both young people and adults. It is suggested that this occurs due to the reduction in the value as well as the scope of emergency aid, as well as the existence of small signs of improvement in the epidemiological situation together with the increase in job vacancies at the end of the year, which may have encouraged the persistence of demand. for work. Finally, the third and final essay has as main objective to investigate the possible existence of the neighborhood effect in the decision of young people from Fortaleza who do not work and do not study, the commonly named “nem-nem” generation. For this, this research innovates by using microdata from the Single Registry (Cadúnico) of the Federal Government, with a great wealth of information for the year 2018, in which it was possible to obtain the georeferenced location of households in a situation of social vulnerability. With this identification, it was possible to use the spatial probit method by Wilhelm and De Matos (2013) based on the model proposed by LeSage et al. (2011), which aims to estimate the situation of desolation among young people residents of the city of Fortaleza. The results showed the need for modeling the neighborhood effect, where young people interact and reinforce labor market and study decisions. Thus, family attributes that favor or inhibit unemployment have direct and indirect effects on the youth subgroup. This externality effect can be incorporated into public policies that favor integrated actions in groups of young people, so that the social multiplier of good decisions is stronger than the reverse effect (vicious).